CZŁOWIEK I ŚMIERĆ – MIĘDZY SEPARACJĄ A BLISKOŚCIĄ - Ochotny, Piotr (Studia Theologica Varsaviensia, 2018)
The author, in his paper, pays close attention to the uncontrolled dialectics of death within human existence; that which is actively experienced but passively sustained; is the end of everything but the beginning of something new; is absolute certainty but unpredictable uncertainty; is always and only personal for me but always and only personal for others, too. In fact, it is very difficult to explain the meaning of death from an ontological study of death: if and how death exists in the area of human experience; if death is an immanent possibility for personal existence or, is it introduced from outwith and occurs when we are not still living. To respond to these questions, the author proposes to use the bridging term, with which various philosophical positions can be qualified. This bridging term is ‘distance’ and our death experience is defined as the distance between man (person acting) and his subject (experience). The dialectical nature of this experience implies that death might be through an infinite separation or an infinite closeness to man. Drifting between those faraway shores, we can find in Emmanuel Levinas’ philosophy. He refers to death as Other (something else for man), but this does not mean that death is strange or unknown within one’s life experience.